Computational drug design of novel COVID-19 inhibitor - Arthur, David Ebuka (2023)
The numerical results of this study are presented in the tables presented below. This has become necessary because of the need to correlate some of the data. Other results, such as plots and pictorial representation of the interactions between the ligands and their receptor binding sites are presented as figures.